Achyrocline satureioides essential oil loaded in nanocapsules ameliorate the antioxidant/oxidant status in heart of rats infected with Trypanosoma evansi. (April 2017) - Souza, Carine F.; Baldissera, Matheus D.; Cossetin, Luciana F.; Dalla Lana, Daiane F.; Monteiro, Silvia G.
Abstract: Oxidative stress has been considered as a pathological mechanism that contributes to initiation and progression of cardiac injury during the Trypanosoma evansi infection. In this sense, the natural compounds with antioxidant and free radical scavenger abilities, such the Achyrocline satureioides essential oil loaded in nanocapsules (AS-NC), may be considered important approach to minimize the cardiac damage. Thus, the aim of this study was to investigate whether AS-NC treatment is able to prevents or reduce the cardiac oxidative damage in infected rats with T. evansi. Heart samples from rats infected by T. evansi showed increased reactive oxygen species (ROS), thiobarbituric reactive-acid substances (TBARS) and glutathione reduced (GSH) levels, while catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities decreased compared with uninfected and untreated animals. Also, the seric biomarkers of cardiac function increased in the infected animals compared with uninfected animals. AS-NC treatment reduced ROS and TBARS levels, ameliorate cardiac CAT and SOD activities of infected rats, and reduced seric biomarkers of cardiac function. AS-NC treatment protected the heart from oxidative stress caused by T. evansi, which might be due to its antioxidant properties. AS-NC might be considered a promising therapeutic agent against oxidative stress, when associated with nanotechnology. Highlights: Trypanosoma evansi impairs cardiac antioxidant/oxidant status. Achyrocline satureioides loaded in nanocapsules prevents cardiac oxidative damage. A. satureioides loaded in nanocapsules reduced seric biomarkers of cardiac function. Protective effect of A. satureioides might be related to antioxidant properties.